Relationship between Early Antibiotic Exposure and Short-Term Growth Velocity in Premature Neonates - Reid, Brittany M.; Eisenberg, Ruth; Forman, Katie; LaTuga, Mariam Susan (American Journal of Perinatology, 2019)
Objective To characterize the relationship between the duration of antibiotic administration during the first week of life and subsequent growth velocity during hospitalization.Study Design This was a retrospective study comparing the inhospital growth of infants born between 30 and 326/7 weeks' gestational age (GA) admitted to the Montefiore Weiler and Wakefield neonatal intensive care units between January 2009 and December 2015. Antibiotic duration during the first week of life was classified as no antibiotics, <5 days of antibiotics, or ≥5 days of antibiotics. Differences between discharge and birth weight Z-scores were compared between the three groups using analysis of variance.Results Of the infants, 87% received antibiotics during the first week of life, with 16% of infants completing ≥5 days. Compared with infants receiving ≤ 5 days of antibiotics, infants treated with ≥5 days had a lower GA, lower Apgar scores, more invasive respiratory support, longer duration of total parenteral nutrition, delayed initiation of enteral feeding, and a higher weight Z-score on admission and discharge (p < 0.05). However, there was no distinction in growth between the three groups assessed by the difference between admission and discharge weight Z-scores (p = 0.64), growth velocity (gram/kilogram/day) (p = 0.104), or an exponential growth velocity outcome (p = 0.423).Conclusion Early antibiotic exposure was not associated with increased growth velocity between birth and discharge. Our study was limited by its retrospective nature and lack of follow-up data postdischarge.
Keywords: growth; antibiotics; prematurity; metabolic syndrome